2006
DOI: 10.1021/bm0600973
|View full text |Cite
|
Sign up to set email alerts
|

Aging Properties of Films of Plasticized Vital Wheat Gluten Cast from Acidic and Basic Solutions

Abstract: In order to understand the mechanisms behind the undesired aging of films based on vital wheat gluten plasticized with glycerol, films cast from water/ethanol solutions were investigated. The effect of pH was studied by casting from solutions at pH 4 and pH 11. The films were aged for 120 days at 50% relative humidity and 23 degrees C, and the tensile properties and oxygen and water vapor permeabilities were measured as a function of aging time. The changes in the protein structure were determined by infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 29 publications
(63 reference statements)
12
88
1
1
Order By: Relevance
“…Protein polymerization properties have, in several studies, been shown to be the main determinant of tensile properties of gluten materials [5,13]. The present study gave very little evidence of any higher degree of polymerization of the rapeseed proteins in the rapeseed residuals used.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Protein polymerization properties have, in several studies, been shown to be the main determinant of tensile properties of gluten materials [5,13]. The present study gave very little evidence of any higher degree of polymerization of the rapeseed proteins in the rapeseed residuals used.…”
Section: Discussioncontrasting
confidence: 65%
“…The most well known of those, being evaluated in a number of studies, is the wheat gluten, a residue from the starch/bioethanol industry and the protein-rich part from wheat after the starch and other carbohydrates have been washed away [11,12]. Gluten residue from the bioethanol industry has a high protein content (around 78%) and is possible to both compression mold and injection mold into materials of relatively high quality in terms of strength and barrier properties [5,13,14]. Examples of other plant proteins that have been reported to have potentials for materials production are soy and corn proteins [8,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…monitored through the decrease in the glycerol upper surface concentration (G-USC), was determined. It was estimated from the ratio of the 850 cm − 1 glycerol peak (Olabarrieta, Gällstedt, Sarasua, Johansson, & Hedenqvist, 2006) to the WG 1525 cm − 1 peak. As shown in Fig.…”
Section: Diameter Of Inhibition Zone (Cm)mentioning
confidence: 99%
“…25,27,28 Besides the plasticizers, additives, such as acids, bases and urea, have been used to improve the processability of WG. 26,[29][30][31] Interestingly, new tetragonal-packed and HCP nanostructures were discovered in the WG with NaOH and ammonium hydroxide (AH) 28 . A similar HCP structure was also reported in the presence of urea, which act as a combined protein denaturant and plasticizer.…”
Section: Introductionmentioning
confidence: 99%